PERAMALAN PASAR BARANG DAN PASAR UANG YANG TERJADI DI INDONESIA KAJIAN PADA MODEL MUNDELL-FLEMING - martin Luter purba; Ade R.Y. Yanti Nababan (Journal of Economic and Business, 2019)
This study aims to look at the effects of shocks that occur in Indonesia using the Mundell-Fleming model. Analysis to see the effects of shocks using the vector autoregression (VAR) model. We chose the VAR model because of the complexity of the economic phenomenon that might occur in the open economy that occurred in Indonesia. The results how the relationship and effects of shocks that occur in gross domestic product, private sector household consumption, direct investment, government consumption expenditure, and net exports occur in Indonesia in the goods market. In addition, this study also examines the relationship and effects of shocks between gross domestic product, the money supply, inflation, and the interest rate that occurs in Indonesia on the money market.